2018
DOI: 10.1002/jcb.26704
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: microRNA‐129‐5p involved in the neuroprotective effect of dexmedetomidine on hypoxic‐ischemic brain injury by targeting COL3A1 through the Wnt/β‐catenin signaling pathway in neonatal rats

Abstract: Our study aims to elucidate the mechanisms how microRNA-129-5p (miR-129-5p) involved in neuroprotective effect of dexmedetomidine (DEX) on hypoxic-ischemic brain injury (HIBI) by targeting COL3A1 through the Wnt/β-catenin signaling pathway in neonatal rats. A total of 120 rats were obtained, among which 15 rats were selected as sham group and rest rats as model, DEX, DEX + negative control (DEX + NC), DEX + miR-129-5p mimics, DEX + miR-129-5p inhibitors, DEX + XAV-939 and DEX + miR-129-5p inhibitors + XAV-939 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Our team of researchers had previously found that miR-129-5p could exercise its protective effect of DEX on neonatal rats with HIBD by regulating the Wnt-catenin signaling pathway by targeting COL3A1. 11 According to the Miranda software, MEG3 could bind to miR-129-5p ( Figure 1A). The dual-luciferase reporter gene assay was utilized to verify the target relationship between MEG3 and miR-129-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Our team of researchers had previously found that miR-129-5p could exercise its protective effect of DEX on neonatal rats with HIBD by regulating the Wnt-catenin signaling pathway by targeting COL3A1. 11 According to the Miranda software, MEG3 could bind to miR-129-5p ( Figure 1A). The dual-luciferase reporter gene assay was utilized to verify the target relationship between MEG3 and miR-129-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Mir-138 affects the formation of fear memory by modifying the expression of the downstream target gene calpain 1 (Capn1) with major implications on the synaptic plasticity. Recently mir-129 has also been associated with memory retention, in addition to its neuroprotective role on hypoxic-ischaemic brain injuries [39]. As shown by Fernandez et al [40] mir-129 and mir-144 play a major role in the modulation of the hippocampal microRNA-mRNA regulatory network upon physical exercise, which eventually lead to improvements in memory detention.…”
Section: Function-and Tissue-specific Expression Of Mirnamentioning
confidence: 96%
“…Previous studies have reported the interaction between DEX and miRNAs in neuroprotection against ischemic hypoxia injury, for examples, Han et al (2018) showed clearly that miR-140-5p enhanced the cerebral protective effects of DEX against HIBD in neonatal rats by directly binding to WNT1 through the negative regulation of the Wnt/β-catenin signal pathway (Han et al, 2018); Wang et al (2019) noticed that DEX could carry out its neuroprotective effects though modulating the relationship between miR2233p and TIAL1; Zhou et al (2018) suggest that miR-129-5p was able to improve neuroprotective role of DEX in HIBI by targeting COL3A1 via Wnt/β-catenin signaling pathway in neonatal rats (Fan et al, 2020). To determine whether miR-206 was implicated in neuroprotection of DEX, we detected the expression of miR-206 in H 2 O 2 and/or DEX treated SK-N-SH cells.…”
Section: Discussionmentioning
confidence: 99%